TOPICAL USE OF GREEN PROPOLIS FOR WOUND HEALING: A SYSTEMATIC REVIEW OF THE LITERATURE (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To systematically identify the effectiveness of the topical use of green propolis in the healing process of surgical wounds. Methods: Systematic review of the literature that considered the publications available in the databases: National Library of Medicine(PubMed/MEDLINE), LatinAmerican and Caribbean Health Sciences Literature (LILACS), The Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Web of Science. The risk of bias of the studies was analyzed using the Systematic Review Centre for Laboratory animal Experimentation (SYRCLE) tool. Results: The four studies analyzed used green propolis for the healing of surgically made lesions. All the selected studies were of experimental methodology, performed with animals. Two studies (50%) used the ethanolic extract of green propolis (at concentrations of 2.4% and 20%) and the other two studies (50%) used the hydroalcoholic extract of green propolis at 5.0%. Conclusion: The results showed that the topical use of formulated products based on green propolis promoted the healing of skin lesions, since it favored angiogenesis, the proliferation of fibroblasts and, consequently, the synthesis and deposition of collagen, as well as showed antimicrobial activity and showed.